Implementation of Turbidity Sensor Based on IoT for Measuring Seawater Turbidity Levels in Gorontalo - Yunus, Muhammad (Jurnal Pijar MIPA, 2026)
Turbidity is the condition of water that is not clear due to suspended particles, such as mud, clay, organic matter, and microorganisms. This research aims to implement an Internet of Things (IoT)- based turbidity sensor to measure seawater turbidity levels in Gorontalo. The IoT-based turbidity sensor system was developed using the SEN-0175 turbidity sensor integrated with an ESP32 microcontroller. The Blynk application serves as a supporting platform for implementing IoT connected to a smartphone. Measurements of seawater turbidity were conducted in three locations in Gorontalo. The result for the first location is an area without residential areas, producing an average turbidity value of 16.5 NTU; the second location is a residential area with several food stalls, producing an average turbidity value of 24.99 NTU; and the third location is a culinary tourism area visited by many tourists, producing an average turbidity value of 50.56 NTU. These results show that the increasing number of human activities in coastal areas has the potential to pollute seawater. Excessive seawater pollution will increase seawater turbidity. Turbidity values exceeding the established seawater quality standards are unsuitable for Marine Tourism and disrupt marine biota; therefore, turbidity concentrations should be no more than 5 NTU. An IoT-based turbidity sensor is suitable for low-cost, real-time monitoring of seawater turbidity in Gorontalo, offering high precision, simple fabrication, and real-time operation.